The inverse of the conditional statement can be made by negating both the hypothesis and the conclusion
The inverse of ur conditional statement is : If my mom does not have to work, then I will not babysit my little sister.
Use the compound amount formula:
A = P*(1+r/n)^(nt)
Here,
A = $3500*(1+0.0375/12)^(12*12) = $5485.24
Answer: slope = 4
Step-by-step explanation:
slope = m = rise/run = y1-y2/x1-x2
9-1/5-3 = 8/2 = 4
There are 72 different ways the director can fill the positions.
(1+2+3+4+5+6+7+8) x 2
You multiply it by 2 because there are going to be 4 other people who will not have a position, and 8/4 is 2.
Answer: She has 1 5/6 exercises for homework.
Step-by-step explanation:
1/2 + 2/3 = 1 1/6
2 * 3 = 6 3 * 2 = 6
1 * 3 = 3 2 * 2 = 4
4 + 3/ 3 + 3
7/6 = 1 1/6
So, she finished 1 1/6 of her problems.
3 - 1 1/6 = 1 5/6
3 - 1 = 2
2 - 1/6 = 1 5/6